HUBUNGAN SIKAP IBU DENGAN PENERAPAN KELUARGA SEHAT DI KELURAHAN SUNGAI LAKAM BARAT KECAMATAN KARIMUN KABUPATEN KARIMUN - Hartati, Hartati; Fitri, Astri Yuni (Universitas Batam, 2019)
Indonesian government policy on community health development in 2015-2019 focuses on establishing primary health care for all citizens. The Healthy Indonesia (Indonesia Sehat) Program is one of the plans for the fifth agenda of Nawa Cita. The data from the family health archives of Indonesia, particularly in Riau Islands Province is noted to be far from satisfaction. Based on the records, it is revealed that 1535 families in Sungai Lakam were categorized in poor health condition confirmed by the Family Health Index of 0.096. This research is an observational analytical study with a cross sectional approach. The result of the univariate analysis indicates 60.6% of the respondents show negative attitude toward the implementation and 68.1% of them do not apply the healthy family principles in daily life. On the other hand, the bivariate analysis confirms a correlation between mother’s attitudes and the implementation of healthy family values at home with p =0.000 (0.000 <0.05). As the suggestion, all parties including medical personnel and commoners to be willing to take roles in promoting and educating the community about the healthy family standards.